Effect of sugar metabolite methylglyoxal on equine lamellar explants: An ex vivo model of laminitis - Vercelli, Cristina (PLoS One, 2021)
Laminitis is one of the most devastating diseases in equine medicine, and although several etiopathogenetic mechanisms have been proposed, few clear answers have been identified to date. Several lines of evidence point towards its underlying pathology as being metabolism-related. In the carbonyl stress pathway, sugars are converted to methylglyoxal (MG)—a highly reactive α-oxoaldehyde, mainly derived during glycolysis in eukaryotic cells from the triose phosphates: D-glyceraldehyde-3-phosphate and dihydroxyacetone phosphate. One common hypothesis is that MG could be synthesized during the digestive process in horses, and excessive levels absorbed into peripheral blood could be delivered to the foot and lead to alterations in the hoof lamellar structure. In the present study, employing an ex vivo experimental design, different concentrations of MG were applied to hoof explants (HE), which were then incubated and maintained in a specific medium for 24 and 48 h. Macroscopic and histological analyses and a separation force test were performed at 24 and 48 h post-MG application. Gene expression levels of matrix metalloproteinase (MMP)-2 and -14 and tissue inhibitor of metalloproteinase (TIMP)-2 were also measured at each time point for all experimental conditions. High concentrations of MG induced macroscopic and histological changes mimicking laminitis. The separation force test revealed that hoof tissue samples incubated for 24 h in a high concentration of MG, or with lower doses but for a longer period (48 h), demonstrated significant weaknesses, and samples were easily separated. All results support that high levels of MG could induce irreversible damage in HEs, mimicking laminitis in an ex vivo model.